The effects of glutamine on hepatic ischemia reperfusion injury in rats - Sözen, S (LITHOGRAPHIA Antoniadis I.-Psarras Th. G.P., 2011)
Aim: To evaluate the effects of glutamine on the hepatic ischemia reperfusion injury in rats. Methods: Thirty rats were divided into three groups as sham (Group 1), control (Group 2), and glutamine(gln) treatment group (Group 3). All rats underwent hepatic ischemia for 45 min followed by 60 min period of reperfusion. Rats were intraperitoneally infused with only 0.9% saline solution in group 2. Rats in group 3 received gln (0.75 g/kg) by intraperitoneal administration, before ischemia and before reperfusion. Blood samples and liver tissues were harvested from the rats, and then the rats were sacrificed. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and lactate dehydrogenase (LDH) levels were determined. Total antioxidant capacity (TAC), catalase (CAT), total oxidative status (TOS), oxidative stress index (OSI) and myeloperoxidase (MPO) in hepatic tissue were measured. Also liver tissue histopathology was evaluated by light microscopy. Results: The levels of liver enzymes in group 3 were significantly lower than those in the group 2. TAC in liver tissue was significantly higher in group 3 than in group 2. TOS, OSI and MPO in hepatic tissue were significantly lower in group 3 than the group 2. Histological tissue damage was milder in the gln treatment group than that in the control group. Conclusion: Our results suggest that gln treatment protects the rat liver against to hepatic ischemia-reperfusion injury.